WORDS AND CULTURE IN PROTOTYPES SEEN IN THE LINGUISTIC RELATIVITY OF Ã¢â‚¬Å“The Cabin in the WoodsÃ¢â‚¬Â MOVIE - NOVI SRIWULANDARI (Fakultas Sastra Universitas Gresik, 2016)
People in this world have everyday languages which consist of related specific and general concepts. Concepts are defined for typical cases (prototypes). This study focused on categorizing the typical instances which appeared in the main charactersÃ¢â‚¬â„¢ utterances into several prototypes in the movie of Ã¢â‚¬Å“The Cabin in the WoodsÃ¢â‚¬Â. This research was descriptive qualitative. The study was conducted by taking pieces of conversation between the main characters. Then, the researcher listed the typical instances of the initial concept including art, furniture, education term, economic term, technology term, animal, clothe, beverage, kitchen set, equipment, building, part of house, part of body, color, stationery, profession, vehicle, drug, jewelry, and natural place. Based on the categorization result, it can be concluded that the most prototypes which were frequently appeared in this movie were the prototypes of part of house (13,3%). It can be occurred, because the setting of this movie was at a rambler in a wood. Therefore, the environment influences the human production of the language, and it is proved that there is a relationship between language, mind, and reality.Ã‚Â Key word: Prototypes